BIM Technology and Material Innovation. The Environmental Dimension - Rossella Franchino; Caterina Frettoloso; Nicola Pisacane (Agathón)
The considerations reported in the following paper take inspiration from interdisciplinary research carried out by authors and relative to the application of BIM technology for the management of the building process. In this regard, the research focuses on the role that this computer technology has in the choice and assessment of the use of different materials while considering their performance in the whole life cycle of the building. In particular, the present work summarizes the role that BIM technology has in the control of the environmental dimension of natural matrix innovative building materials. This evaluation is pursued through the processing of a set of criteria able to describe the quality of a given material especially in terms of compatibility.